A 20-year perspective on the Ottawa Ankle Rules: Are we still on solid footing?. Issue 7 (July 2021) - Herman, Lawrence
Abstract : ABSTRACT: The Ottawa Ankle Rules, finalized in 1995, are a clinical decision directive for the use of radiographs in patients with traumatic ankle and foot injuries. The researchers who developed the rules defined clinically insignificant ankle fractures as distal fibular or malleolar chip fractures of 3 mm or less. They concluded that at least one-third of all ankle and foot radiographs could be eliminated by using their rules, which have since been adopted as the standard of care in EDs. This article explores whether, after more than 20 years in use, the Ottawa Ankle Rules are still valid, and whether they should continue to be used or be replaced by a superior protocol.